HUBUNGAN KELINCAHAN TERHADAP KEMAMPUAN MENGGIRING BOLA PADA TIM FUTSAL SMP NEGERI 32 PEKANBARU - Wahyudi Wahyudi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this study was the players of the team were not optimal when dribbling the ball.While dribbling is a basic technique which is often done byfutsal players to an opponent team to defeat them like doing sprint while dribbling the ball.When dribbling the ball, the position of players were too close to the position of opponent player or the ball being led too far from the position of the player so that the opponent player was easy to grab the ball, the ball should be in control of the player as a result the opponent team was difficult to get the ball. This was presumably because of the speed possessed by futsal player SMP 32 Pekanbaru. The purpose of this research was to determine whether there was a relationship of the speed with the ability to dribble the ball at Futsal Team of SMPN 32 Pekanbaru. The population in this study were Futsal players of SMP 32 Pekanbaru which consisted of 12 people. A sampling technique was the overall population (total sampling). The Instruments used in this research was dooging test run, which aimed to measure the speed and then test the dribble that aimed to find out how big the dribbling ability of the sample used. After that, the data was analyzed to test for normality test at significant level a0,05 lilifors. Based on the research results, it can be concluded as follows. From the results obtained, the speed has a relationship with the dribbling ability Futsal team SMP 32 Pekanbaru in dribbling ability where Tcount at significant level α (0,05) = 0.602, it means Tcount (0.681)> Ttab (0.602) Keywords : The Speed, Dribbling Ability.